Oral cannabinoids in people living with HIV on effective antiretroviral therapy: CTN PT028—study protocol for a pilot randomised trial to assess safety, tolerability and effect on immune activation. Issue 1 (17th January 2019) - Costiniuk, Cecilia T; Saneei, Zahra; Routy, Jean-Pierre; Margolese, Shari; Mandarino, Enrico; Singer, Joel; Lebouché, Bertrand; Cox, Joseph; Szabo, Jason; Brouillette, Marie-Josée; Klein, Marina B; Chomont, Nicolas; et al.
Abstract : Introduction: Despite antiretroviral therapy (ART), people living with HIV have higher rates of non-infectious chronic diseases. These conditions are driven by relatively high levels of inflammation persisting on ART compared with uninfected individuals. Chronic inflammation also contributes to HIV persistence during ART. Cannabis when taken orally may represent a way to reduce inflammation and strengthen immune responses. Before planning large interventional studies, it is important to ensure that cannabis taken orally is safe and well tolerated in people living with HIV. We propose to conduct a pilot randomised trial to examine the safety and tolerability of cannabis oils containing tetrahydrocannabinol (THC) and cannabidiol (CBD) consumed orally in people living with HIV. We will also measure inflammatory markers, markers of HIV persistence in peripheral blood cells and changes in the gastrointestinal microbiome. Methods and analysis: Twenty-six people living with HIV having undetectable viral load for at least 3 years will be randomised to receive TN-TC11LM (THC:CBD in 1:1 ratio) or TN-TC19LM (THC:CBD in 1:9 ratio) capsules daily for 12 weeks. Safety and tolerability of these capsules will be assessed through haematological, hepatic and renal blood tests, face-to-face interviews and questionnaires. Proportions of participants without any signs of significant toxicity (grades 0–2 scores on the WHO toxicity scale) and who complete the study, as well as scores on quality of life and mood will be examined using descriptive statistics. The effects on inflammatory markers, markers of peripheral blood reservoir size and effect on the composition of the gastrointestinal microbiome will be assessed before and after study completion. Ethics and dissemination: This study has been approved by the Research Institute of the McGill University Health Centre. A Data Safety Monitor will review safety information at regular intervals. The final manuscript will be submitted to an open-access journal within 6 months of study completion. Trial registration number: NCT03550352 .